KAFAAH DALAM PERNIKAHAN UNTUK MEMBENTUK KEHARMONISAN RUMAH TANGGA - Mazaya, Ayda; Laeliyah, Rokhu Dlotul; Hami, Widodo (Al-Usroh : Jurnal Hukum Keluarga Islam, 2024)
Islam encourages forming a family, marriage is His Sunnah. Marriage is also a servant's way of getting closer to the Creator, provided that he marries the right person. Because family is like a small picture in life that fulfills human desires, without eliminating needs. This research uses qualitative research methods with a literature study approach. Research findings show that forming a harmonious and harmonious family is everyone's desire. Marriage is not only about fulfilling instincts and sharing material desires, but more than that there are various tasks that must be fulfilled, both psychologically, spiritually and socially which must be responsibilities. Including things that must be fulfilled, namely Kafa'ah. Kafa'ah in marriage, according to Islamic legal terms, is balance and harmony between the prospective wife and husband in terms of social, moral and economic levels, so that each candidate does not find it difficult to enter into marriage. Kafa'ah in marriage regarding household harmony is seen from several criteria that are taken into consideration, such as religion, lineage, assets, profession and also physical absence of defects. The influence of kafa'ah in marriage can be seen from several criteria in choosing a life partner.